Global eHealth capacity: secondary analysis of WHO data on eHealth and implications for kidney care delivery in low-resource settings. Issue 3 (23rd March 2022) - Okpechi, Ikechi G; Muneer, Shezel; Ye, Feng; Zaidi, Deenaz; Ghimire, Anukul; Tinwala, Mohammed M; Saad, Syed; Osman, Mohamed A; Lunyera, Joseph; Tonelli, Marcello; Caskey, Fergus; George, Cindy; et al.
Abstract : Objective: To describe the use of electronic health (eHealth) in support of health coverage for kidney care across International Society of Nephrology (ISN) regions. Design: Secondary analysis of WHO survey on eHealth as well as use of data from the World Bank, and Internet World Stats on global eHealth services. Setting: A web-based survey on the use of eHealth in support of universal health coverage. Participants: 125 WHO member states provided response. Primary outcome measures: Availability of eHealth services (eg, electronic health records, telehealth, etc) and governance frameworks (policies) for kidney care across ISN regions. Results: The survey conducted by the WHO received responses from 125 (64.4%) member states, representing 4.4 billion people globally. The number of mobile cellular subscriptions was <100% of the population in Africa, South Asia, North America and North East Asia; the percentage of internet users increased from 2015 to 2020 in all regions. Western Europe had the highest percentage of internet users in all the periods: 2015 (82.0%), 2019 (90.7%) and 2020 (93.9%); Africa had the least: 9.8%, 21.8% and 31.4%, respectively. The North East Asia region had the highest availability of national electronic health record system (75%) and electronic learning access in medical schools (100%), with the lowest in Africa (27% and 39%, respectively). Policies concerning governance aspects of eHealth (eg, privacy, liability, data sharing) were more widely available in high-income countries (55%–93%) than in low-income countries (0%–47%), while access to mobile health for treatment adherence was more available in low-income countries (21%) than in high-income countries (7%). Conclusion: The penetration of eHealth services across ISN regions is suboptimal, particularly in low-income countries. Increasing utilisation of internet communication technologies provides an opportunity to improve access to kidney education and care globally, especially in low-income countries.